A trans-national examination of the impact of the COVID-19 pandemic on abortion requests through a telemedicine service. Issue 3 (1st November 2021) - van Ooijen, Liën Trudi; Gemzell-Danielsson, Kristina; Waltz, Mitzi; Gomperts, Rebecca
Abstract : Background: The COVID-19 pandemic is limiting access to reproductive healthcare worldwide. Substantial research gaps remain regarding the impact of the pandemic on access to abortion care. Methods: We performed a cohort analysis of abortion requests made through the telemedicine abortion service Women on Web (WoW) between 18 March 2020 and 4 May 2020. We used binary logistic regression analyses to test the association between COVID-19 as a reason for the help request and reporting having had an ultrasound to determine gestation and/or use of contraception. A subanalysis of Italy, Argentina, Malaysia and the United Arab Emirates (UAE) was executed to explore differences between countries. Results: Of requests made during the study period, 43.5% (n=1972) were COVID-19-related. A negative association was found with having had an ultrasound to determine gestation length and COVID-19-related requests. Italy had the highest percentage (66.5%, n=117) of COVID-19-related requests in the subanalysis, followed by Argentina (55.3%, n=68), Malaysia (51.9%, n=41) and the UAE (44.4%, n=75). Conclusions: Almost half the women and pregnant people having an abortion through WoW reported experiencing obstacles to abortion care because of COVID-19. Abortion guidelines should be updated to permit abortion services via telemedicine. This is especially urgent during the ongoing pandemic.